English Explorers in the East (1738-1745) : The Travels of Thomas Shaw, Charles Perry and Richard Pococke - Finnegan, Rachel, (Middle East and Islamic Studies E-Books Online, Collection 2019, ISBN: 9789004386341., 2019)
In English Explorers in the East (1738-1745). The Travels of Thomas Shaw, Charles Perry and Richard Pococke , Rachel Finnegan offers an account of the influential travel writings of three rival explorers, whose eastern travel books were printed within a decade of each other. Making use of historical records, Finnegan examines the personal and professional motives of the three authors for producing their eastern travels; their methods of researching, drafting, and publicising their works while still abroad; their relationships with each other, both while travelling and on their return to England; and the legacy of their combined works. She also provides a survey of the main features (both textual and visual) of the travel books themselves.